CSI: Crime Scene Investigation Season 3 Disc 2 Episodes : 13 - 23 - Anthony, E. Zuiker; Eric Szmanda Gary Dourdan George Eads Jorja Fox Marg Helgenberger Robert David Hall William L Petersen (USA, Canada Jerry Bruckheimer Television, 2002)
This show follows the nights of the detectives working at the Las Vegas Police Department Crime Scene Investigations bureau. Being the second busiest crime lab in America, CSI officers use the best scientific and technical methods to solve puzzles and catch criminals.
An elite team of police forensic evidence investigation experts work their cases in Las Vegas.
Languages: English Subtitles: English
Keywords: Drama -- Mystery -- Thriller -- Tv Series -- Crime